Current Status of Seaweed Diversity and Distribution on Tu Thien Intertidal Rocky Platform in Ninh Thuan Province, Vietnam - Dang, Luat Minh; Nguyen, Yen Thi Kim; Le, Trinh Bui Trung (Tropical Natural History, 2025)
The study investigated the diversity and the spatial distribution of seaweed in the intertidal zone during three periods including December 2022, March 2023, and May 2023 at Tu Thien seaweed field, Phuoc Dinh commune, Thuan Nam district, Ninh Thuan province. Samples were hand collected through wading surveys of the intertidal zone during low tide periods. The coverage was assessed based using the line transect-quadrat method of Saito and Atobe. The investigation recorded 59 species of seaweeds belonging to 3 phyla, 3 classes and 34 genera. Among all families, Sargassaceae was the most species-rich with 11 species, followed by Gracilariaceae with 9 species. The Rhodophyta accounted for the highest proportion of species composition. The highest coverage of seaweed was measured in March 2023 (103.36 to 343.19). Ulva reticulata was the dominant species, with the Simpson dominance index ranging from 0.7 to 0.9 at most sites in March. Simultaneously, the coverage of this species reached 80% during the March survey period. The Cheney index of 2.28, the Tu Thien seaweed community was classified as temperate. It is inferred that seaweed exhibits substantial diversity and abundance at optimal times of the year, particularly during the first half, before gradually diminishing in the latter half. The baseline data generated in this study will serve as the first foundational reference, not only for the scientific assessment of seaweed coverage but also for documenting the occurrence of seaweed species in the Tu Thien seaweed field, Ninh Thuan.